A software-hardware optimizer model for optimized design of things in Agents of Things - Mzahm A.M.; Ahmad M.S.; Tang A.Y.C.; Ahmad A. (Asian Research Publishing Network, 2023)
The machines, or things in the Internet of Things (IoT) lack self-reasoning capability, which limits their potential to provide value-added services for humans. Consequently, we introduce the concept of Agents of Things (AoT) as an extension to the IoT, in which the things are embedded with self-reasoning intelligent software agents to provide value-added services for humans. Two crucial issues in designing intelligent things are to determine what value-added services they should offer and the subsequent level of reasoning abilities that are required for these services. Consequently, we need to find an optimum match between the hardware capabilities of the things and their corresponding software agents reasoning abilities to deliver value-added services on top of performing their basic IoT functions. In this paper, we present the results of a software analysis represented by a software spectrum and a hardware analysis represented by a hardware spectrum. We then link these two spectra to form a structured hardware-software optimizer for a things design model, which we called the Structured Hardware-Software Optimizer or SHOM. We demonstrate the use of SHOM in designing optimized things in a simulated traffic scenario in manifesting the AoT concept. 2005 - 2016 JATIT & LLS. All rights reserved.